2020
DOI: 10.1371/journal.pgen.1008317
|View full text |Cite
|
Sign up to set email alerts
|

RNA Polymerase II CTD phosphatase Rtr1 fine-tunes transcription termination

Abstract: RNA Polymerase II (RNAPII) transcription termination is regulated by the phosphorylation status of the C-terminal domain (CTD). The phosphatase Rtr1 has been shown to regulate serine 5 phosphorylation on the CTD; however, its role in the regulation of RNAPII termination has not been explored. As a consequence of RTR1 deletion, interactions within the termination machinery and between the termination machinery and RNAPII were altered as quantified by Disruption-Compensation (DisCo) network analysis. Of note, in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 114 publications
(199 reference statements)
1
34
0
Order By: Relevance
“…Rtr1 ("regulator of transcription" 1) has been described as a phosphorylated RNA pol II interactor by acting as an S5-P CTD phosphatase during the transition from the initiation of the transcription to elongation in vivo (Gibney et al, 2008;Mosley et al, 2009Mosley et al, , 2013Hsu et al, 2014;Smith-Kinnaman et al, 2014;Hunter et al, 2016). Additional roles have been proposed for Rtr1 in transcription and mRNA stability (Mosley et al, 2013;Hsu et al, 2014;Hodko et al, 2016;Victorino et al, 2020) (our unpublished data).…”
Section: Rtr1/rpap2mentioning
confidence: 82%
“…Rtr1 ("regulator of transcription" 1) has been described as a phosphorylated RNA pol II interactor by acting as an S5-P CTD phosphatase during the transition from the initiation of the transcription to elongation in vivo (Gibney et al, 2008;Mosley et al, 2009Mosley et al, , 2013Hsu et al, 2014;Smith-Kinnaman et al, 2014;Hunter et al, 2016). Additional roles have been proposed for Rtr1 in transcription and mRNA stability (Mosley et al, 2013;Hsu et al, 2014;Hodko et al, 2016;Victorino et al, 2020) (our unpublished data).…”
Section: Rtr1/rpap2mentioning
confidence: 82%
“…Previously performed experiments found that the entire CPF complex copurifies with FLAG-tagged Pta1 35 . In theory, addition of an affinity purified CPF sample to one channel of the TMT multiplex would increase the MS1 ion intensity of CPF subunits and would “trigger” the mass spectrometer to pick peptides from CPF complex subunits more often in a DDA analysis than in samples that lack an isobaric trigger.…”
Section: Resultsmentioning
confidence: 99%
“…To boost detection of the native CPF subunits, subsequent mTPP replicates of WT and ssu72-2 included the addition of a trigger channel consisting of an affinity-purified CPF complexes. Affinity purification of CPF via Pta1-FLAG was performed as described previously for Ssu72-FLAG purifications 35 . The Pta1-FLAG affinity purified sample was added at a ratio of 6.25 ug trigger to 50 ug of the lowest heat-treated sample (1:8 ratio) for the initial study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Affinity purification of native CPF via Pta1-FLAG was performed as described previously for Ssu72-FLAG purifications. 37 The Pta1-FLAG affinity-purified sample was added at a ratio of 6.25 μg trigger to 50 μg of the lowest heat-treated sample (1:8 ratio) for the biological replicates. The untreated samples were removed from the multiplex from no trigger samples to accommodate for the isobaric trigger channel to be labeled with TMT126.…”
Section: Experimental Sectionmentioning
confidence: 99%